PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON EQUITY TERHADAP FINANCIAL DISTRESS - Chairani Nurhamidah; Kosasih (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2021)
Financial distress is a situation where the company is unable to pay off its debts. This research uses purposive sampling technique. The data analysis method used is logistic regression analysis. The data were processed using SPSS 25 software. The results of this study indicate that: (1) Current ratio has a negative and significant effect on financial distress in textile and garment sub-sector manufacturing companies listed on the Indonesian stock exchange with a coefficient value of -5.661 and a significance value of 0.047 < 0.05. (2) Debt to equity ratio has a negative and insignificant effect on financial distress in textile and garment sub-sector manufacturing companies listed on the Indonesian stock exchange with a coefficient value of -0.008 and a significance value of 0.984 > 0.05. (3) Return on Equity has a negative and insignificant effect on financial distress in textile and garment sub-sector manufacturing companies listed on the Indonesian Stock Exchange with a coefficient value of -2.796 and a significance value of 0.605 > 0.05. (4) Current Ratio, Debt To Equity Ratio, and Return On Equity simultaneously affect financial distress in textile and garment sub-sector manufacturing companies listed on the Indonesian stock exchange with a chi-square value of 23.863 and a significant value of 0.000 <0.05.